INVESTIGATION OF SUITABLE CATHODES FOR THE PRODUCTION OF HYDROGEN GAS BY ELECTROLYSIS - YAZICI, B; TATLI, G; GALIP, H; ERBIL, M (Pergamon-Elsevier Science Ltd, 1995)
The anodic and cathodic behaviours of aluminium, iron, mercury steel (HgSt), chrome-nickel steel (CrNiSt) and platinum have been studied in a 2N NaCl electrolyte (pH = 5) by means of electrolysis. The potentials of the cathodes and the theoretical and experimental discharge potentials of the systems have been determined. The cathodic and anodic overpotentials produced on Al, Fe, HgSt, CrNiSt and Pt were predicted against a platinum anode and a platinum cathode, respectively. The amounts of hydrogen gas produced at different times on the cathodes at a constant potential were measured and the hydrogen yield was calculated. From the data obtained, it is suggested that Pt anode and Al or HgSt cathode, or Al anode and Pt cathode, couples should be employed for the best electrolysis system.
Keywords: Alkaline-Solutions; Evolution; Aluminum; Electrocatalysts; Polarization; Environment; Energy